Kramers Weyl semimetals as quantum solenoids and their applications in spin-orbit torque devices - Wen-Yu He (Nature Portfolio, 2021)
A Kramers Weyl semimetal has a chiral crystal structure and is thought to exhibit unique physical properties due to the chiral lattice symmetry. Here, the authors theoretically demonstrate that this class of material can exhibit a strong longitudinal magnetoelectric response that could be used for magnetic switching in a ferromagnetic system.